ANALISA PENERAPAN K3L INDUSTRI PAKAIAN JADI DI INDONESIA MELALUI METODE LITERATURE REVIEW - Sarnadi, Sarnadi; Santoso, Sugeng (Transpublika Publisher, 2023)
The apparel industry in Indonesia is a labor-intensive industry capable of absorbing a very large workforce. According to BPS (Central Statistics Agency) data in 2020, proportion of the workforce in the manufacturing industry sector, the industry accounts for 1.81% of the workforce out of a total of 13.61% of the total workforce or is in second place after the food industry. With a very large number of workers, it is only fitting that K3L be a common concern. Method for this research is using of literature review method, using secondary data sources originating from national journals related to the K3L application in the apparel industry. The result of sorting several journals obtained journals as many as 10 research journals. Purpose of this research is to analyze the implementation of K3L in the apparel industry so that a broader picture of this implementation will be obtained. Based on the result of research, the conclusion can be gain are: 1) the number of research that related with occupational health and the environment in the apparel industry in Indonesia is still limited. Meanwhile, there are many journals related to work safety, 2) related with the application of work safety in the apparel industry in Indonesia, showing good implementation results, 3) in terms of work accident risk, it is more related to risk identification and risk analysis, while evaluation and risk control are still lacking.